INTEGRATION OF ACADEMIC EDUCATION AND SPIRITUAL GUIDANCE AT PKBM BUDI LUHUR - Alip Fikri Abdillah; Khoirurrozikin; Kufita Indi Zulfa; Layla Mardhliyah (JURNAL ASIK, 2026)
Community Learning Activity Centers (PKBM) are a strategic solution for providing equivalency education. This study aims to analyze the innovative boarding school-based PKBM model at PKBM Budi Luhur Purwokerto, which integrates academic learning (Packages A, B, and C, PAUD-TK) with spiritual and character development. This study used observation and descriptive qualitative research methods to identify programs, resource management (human resources and finance), and work program management of the institution. The results showed that PKBM Budi Luhur successfully implemented the concept of integrated education, supported by simple yet effective resource management. The head of PKBM applies a transformational leadership style oriented towards religious values. The work program is managed in a participatory manner, applying a continuous improvement (PDCA) approach, and includes superior life skills programs such as basreng-making training. In conclusion, this PKBM is a model of good practice in providing non-formal education based on religious values, producing intelligent, independent, and moral graduates.